Gminna pomoc publiczna przedsiębiorcom po wejściu Polski do Unii Europejskiej - przykład Jeleniej Góry - Maciejuk, Marian (Public Aid Provided to Businesses by Municipalities after Poland's Accession to the European Union - the Example of Jelenia Góra, 2006)
The article identifies the public aid offered to SME after Poland's accession to the EU from the point of view of the Polish communes (gminas) as donors of such an aid. It gives the legal basis for public aid and forms of such aid as granted by the Polish communes to business entities. It also presents a case study of public aid in Jelenia Góra in the 2002-2005 period, covering the size and structure of public aid with respect to the number and size of business entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 420-428